2017
DOI: 10.2147/ijn.s139215
|View full text |Cite
|
Sign up to set email alerts
|

Copper nanoparticle-induced ovarian injury, follicular atresia, apoptosis, and gene expression alterations in female rats

Abstract: Numerous studies have reported the accumulation of copper nanoparticles (Cu NPs) in organs and the corresponding damage, although whether Cu NPs can be translocated to the ovaries and their ovarian toxicity are still unknown. In this study, three groups of female rats were injected with 3.12, 6.25, or 12.5 mg/kg Cu NPs for 14 consecutive days. The pathological changes, hormone levels, apoptosis and apoptotic proteins, oxidative stress, and gene expression characteristics in the ovaries were then investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 55 publications
4
31
0
Order By: Relevance
“…Additionally, Sizoval et al indicated that exposure to Cu‐NPs could induce apoptosis or necrosis in different types of cells or organs, such as the liver and kidney. Recently, our research team showed that the intraperitoneal injection of Cu‐NPs at 12.5 mg/kg/d could induce ovarian atresia and apoptosis in rats . The findings of the present study were consistent with those of earlier studies, and further indicate that Cu‐NPs induce oxidative stress and activate apoptosis‐related proteins, leading to uterine injury.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Additionally, Sizoval et al indicated that exposure to Cu‐NPs could induce apoptosis or necrosis in different types of cells or organs, such as the liver and kidney. Recently, our research team showed that the intraperitoneal injection of Cu‐NPs at 12.5 mg/kg/d could induce ovarian atresia and apoptosis in rats . The findings of the present study were consistent with those of earlier studies, and further indicate that Cu‐NPs induce oxidative stress and activate apoptosis‐related proteins, leading to uterine injury.…”
Section: Discussionsupporting
confidence: 92%
“…Sarkar et al reported that copper nanomaterial induces oxidative stress and apoptosis in the kidney via both the extrinsic and intrinsic pathways. Similarly, we recently found that ovarian apoptosis induced by exposure to Cu‐NPs (12.5 mg/kg/d) occurred through both the extrinsic and intrinsic pathways . Taken together, these findings strongly indicate that exposure to Cu‐NPs (12.5 mg/kg/d) induces uterine tissue apoptosis via both the extrinsic (mitochondria‐independent) and intrinsic (mitochondria‐induced) apoptotic pathways.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations